2022
DOI: 10.33545/pathol.2022.v5.i1a.446
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of endometrium in hysterectomy specimens from cases of abnormal uterine bleeding

Dr. Dhruvi Shah,
Dr. Mansi J Savsaviya,
Dr. Nutan P Patel

Abstract: Introduction:In India, the prevalence of women suffering from abnormal uterine bleeding is around 17%. Dilatation and curettage, endometrial biopsy and hysterectomies play an important role in diagnosis as well as treatment of abnormal uterine bleeding cases. Though number of minimaly invasive surgical options available, hysterectomy remains the widely accepted and practiced treatment of choice. Therefore those cases where causes of bleeding cannot be determined clinically then histological examination of hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studies have reported different incidence rates of endometrial carcinoma due to the variation in the geographical location, lifestyle, socioeconomic conditions, as well as their inclusion criteria. 1 We found chronic endometritis in 5 (1.2%) women, most commonly seen in the premenopausal age group (0.7%), due to abortions, intra-uterine contraceptive devices, and ascending route of infections.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Previous studies have reported different incidence rates of endometrial carcinoma due to the variation in the geographical location, lifestyle, socioeconomic conditions, as well as their inclusion criteria. 1 We found chronic endometritis in 5 (1.2%) women, most commonly seen in the premenopausal age group (0.7%), due to abortions, intra-uterine contraceptive devices, and ascending route of infections.…”
Section: Discussionmentioning
confidence: 75%
“…25 In a study by Dhruvi et al, endometrial polyps were found in 2% of women. 1 A polyp is a focal hyperplastic overgrowth of endometrial glands and stroma around a vascular core in the uterine cavity. 26 Possible etiologies include genetic, biochemical, and hormonal factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations